Sociodemographic and Clinical Factors of Acute Ischemic Stroke (Bangladesh Journal of Neuroscience, 2017)
An observational study was carried out to analyze prevalence of risk factors for ischemic stroke in hospitalized patient in a university hospital. Ninety patients were chosen by using purposive sampling technique. The mean age of patients was 59.01±9.87 years varied from 30 to 75 years and male to female ratio was 1.2:1. Highest incidence of stroke was between the 6th and 7th decade. Patients came from both rural 49 (54.4%) and urban 41 (45.6) area. Most of them belonged to the lower-middle group 70 (84.8%). Regarding education 47 (52.2%) patients had primary level education and 8 (8.9%) patients were illiterate. It was observed that among them current smoker were 30 (33.3%) and ex-smoker 17 (18.9%). It was also observed that 52 (57.8%) patients had hypertension and 32 (35.6%) had diabetes mellitus (DM). Ischemic heart disease was present in 14 (15.6%) patients. By Oxford shire classification of stroke, it was observed that PAC is common 51 (56.7%) among all forms. Majority 38 (42.2%) of patients had hospital stay of 11-15 days. The mean hospital stay was found 13.68±6.6 days. This study found that cigarette smoking, hypertension, diabetes mellitus and ischemic heart diseases are the major risk factors prevalent in our community while other risk factors demand further study.Bangladesh Journal of Neuroscience 2017; Vol.  33 (1): 18-23